Electricity Supply Interruptions in the Philippines: Characteristics, Trends, Causes - Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2022)
Electricity serves as a vital input to modern economies. Many critical infrastructures such transportation, telecommunications, banking, among others, depend on continuous supply of electricity to perform their functions. However, as modern economies continue to move towards digitalization and adoption of technologies, part of the population still deals with electricity supply interruptions, which greatly hinders productivity. In this study, we analyzed the monthly interruption reports of Electric Cooperatives submitted to the National Electrification Administration to uncover some interesting trends related to electricity supply interruptions in the Philippines. The analysis provides a fundamental landscape for understanding the intricacies of supply interruptions for the benefit of formulating more appropriate and realistic policy recommendations for the power sector. It also sets direction for future research work. Overall, the results of this study show that the causes of electricity supply interruptions in the country can be broadly categorized into environment, supply, and technical issues.
Keywords: 330; electric power industry; electric cooperatives; electric power infrastructure; power interruptions; electricity supply; energy policy